Load distribution in instrumented cohesion piles A case study of E45 Gullbergstunneln - STAFSTRÖM, YLVA; STAXÄNG, ELON (My University, 2023)
This thesis investigates the load distribution in three instrumented precast concrete cohesion piles installed in a tunnel project in Gothenburg, Sweden. The piles are supporting a tunnel and will furthermore support 10-14 story buildings planned on top of the tunnel. The piles are instrumented with Sister Bar strain gauges, which were used to estimate the load distribution in the piles. The results show that the piles have been subject to tension forces after driving, but the load distribution shows a tendency towards compression over time. To compare the findings from the data analysis, hand calculations using the α and β-methods were used to estimate the theoretical load distribution in the case study piles. This was done for both a heaving and a settling soil matrix. Additionally, a numerical analysis was used to investigate the load distribution for a pile subject to unloading and mass displacement from nearby piling. The results show that development of significant tension forces is possible due to nearby piling. Comparison between data analysis, hand calculations and the numerical model show a resemblance in the shape of the load distribution.
Keywords: Instrumented piles, Sister Bars, strain gauges, load distribution, heave, drag load, negative, positive, skin friction.